ANALISIS KESALAHAN SISWA PADA MATERI ALJABAR DITINJAU DARI KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS - Omiyati Oman Putri; Lessa Roesdiana (IKIP Siliwangi, 2023)
This research was conducted based on the results of observations. Many students still make mistakes in solving math problems which have an impact on their ability to understand mathematical concepts. This research is a descriptive research with a qualitative approach. The subjects of this study were Grade VIII students and had a sample of 38 students who were selected by purposive sampling on students with high, medium, and low ability levels and focused on algebraic material. The instrument used in data collection was a test instrument for understanding mathematical concepts in the form of a description of 7 questions. Data were analyzed with a rubric of 3 scale which was processed using Microsoft Excel 2010 (Version 14.0). The results showed that in solving algebraic problems students made many mistakes due to lack of thoroughness and carelessness of 16 students, 13 students made conceptual errors, 12 students made process skill errors, 7 students made notation errors, and 7 students made mistakes. understand the questions as many as 6 students. Factors that cause these errors are the lack of attention in solving problems, students' reluctance to participate in the learning process, and students' understanding of algebra material.